Development of Spirituality in School Age and Its Relevance to Education Islam - Trysha Yulindaputri; Eva Latipah (Insight School Academy, 2023)
The problem that arises today is the occurrence of a crisis of spirituality in children and adolescents. Not infrequently, children commit crimes such as robbery, gambling, brawls between schools, murder, drug addiction, and others. This is due to the need for a balance between religious values in individuals with the development of an increasingly advanced era. This study aims to analyze the effect of spirituality during school age and its relevance to Islamic education. This study uses qualitative research with a case study approach. Data collection techniques in this study were observation, questionnaires, and documentation. Data analysis techniques in this study include data reduction, presenting data, and drawing conclusions. The results showed that there are six stages of spiritual development, namely the stage of intuitive-projective beliefs (early childhood), mystical-literal beliefs (middle and late youth), synthetic-conventional beliefs (transition between childhood and adolescence, adolescence early), individual-reflective ideas (the transition between adolescence and adulthood, early adulthood), conjunctive beliefs (mid-adulthood), and universal beliefs (mid-adult or late adulthood). Children's religious attitudes should be formed early, starting from the child's closest environment, such as family, school, and community. The stronger the child's experience, the better the development of children's religious attitudes can be controlled optimally.